Ecolabelling of Seafood - Phillips, Bruce; Ward, T. (Mexican Fisheries Society, 2009)
Ecolabelling provides consumers with the opportunity to make informed choices about the seafood they purchase, at the fresh fish bar, in supermarkets, cafes and restaurants. A recent book Seafood Ecolabelling: Principles and Practice deals with seafood, both farmed and wild capture, and describes various forms of consumer programs such as ecolabelling, guides and rating systems, with a worldwide focus. The book presents ecolabelling concepts and issues from a broad perspective so that seafood consumers, resellers, processors and fishers can be better informed about the role and quality of individual seafood ecolabels they may encounter and enable them to make more meaningful decisions about the costs and benefits of ecolabelled seafood and certification systems. In particular, each chapter provides an analysis of the topic in terms of the history and development, and identifies aspects that are considered to have been keys to successes. The final theme provides perspectives from an analysis of what our short experience with seafood market-based incentives predicts for the future of sustainable seafood and the health of ocean ecosystems.